The Influence of Empowering Leadership and Artificial Intelligence on Innovative Behavior Mediated by Employee Engagement - Viktoria Mistika Animus; Feivel Rick Cavanaugh Huang; Netania Emilisa (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of empowering leadership and artificial intelligence on innovative behavior with employee engagement as a mediating variable among state-owned banks employees in Central Jakarta. The research design refers to prior studies and employs a descriptive quantitative approach using hypothesis testing. Data were collected cross-sectionally from October to November 2025 through an online questionnaire, generating both primary and secondary data. Purposive sampling was applied with criteria targeting millennial employees working in the banking sector, resulting in a total sample of 150 respondents. The findings indicate that empowering leadership, artificial intelligence, employee engagement, and innovative behavior are all perceived at a moderately high level. The results further reveal that empowering leadership positively influences both innovative behavior and employee engagement, whereas artificial intelligence does not positively influence innovative behavior but does positively influence employee engagement. Additionally, employee engagement has a positive effect on innovative behavior and fully mediates the relationship between empowering leadership and artificial intelligence toward innovative behavior. These findings highlight the critical role of employee engagement in enhancing the impact of leadership and technological adoption on employees’ innovative behavior.